Preparation of Soft Magnetic Fe-Ni-Sb-B Nanoalloy by Solid-Solid Reaction - Zhong*, Guoqing; Zhong, Qin (Asian Journal of Chemistry, 2013)
The Fe-Ni-Sb-B amorphous alloy has been prepared by a solid-solid chemical reaction of ferric trichloride, nickel chloride, antimony chloride and potassium borohydride powders at room temperature. The inductive couple plasma study indicates that the resultant is composed of Fe 5.38 %, Ni 56.19 %, Sb 29.02 % and B 0.44 %. The XRD and thermal analysis show that the alloy is a non-strict sense amorphous alloy which constituted with NiSb and FeNiB. The TEM image shows the resultant is spheroidicity particles which average size is estimated to be 20-30 nm. The mole ratio of the metal salts has been determined to be 1.0:1.0:0.25 to get the amorphous alloy. The largest saturation magnetization value of the 17.35 emu/g is obtained.